Efficient triplet–triplet annihilation upconversion in binary crystalline solids fabricated via solution casting and operated in air. Issue 1 (2nd November 2016) - Kamada, Kenji; Sakagami, Yusuke; Mizokuro, Toshiko; Fujiwara, Yutaka; Kobayashi, Kenji; Narushima, Kaishi; Hirata, Shuzo; Vacha, Martin
Abstract : Binary crystalline solids via solution casting under rapid drying conditions were found to show efficient triplet–triplet annihilation upconversion by suppressing the segregation of the components. Abstract : Binary crystalline solids consisting of a sensitizer (Pt-octaethylporphyrin) and an emitter (9, 10-diphenylanthracene (DPA) or its alkyl-strapped derivative (C7-sDPA)) were fabricated by solution casting under rapid drying conditions and found to show efficient triplet–triplet annihilation upconversion by the suppression of component segregation. Microspectroscopic studies of individual crystalline particles of the binary solids revealed threshold intensities as low as 5 mW cm −2, close to solar levels, and UC quantum yields of 20% were possible when using C7-sDPA as an emitter, even in air.